(untitled) (Journal of Misan Researches, 2023)
This research entitled “The Construction of the Andalusian Poem in the Nabhaniyy Collectio: Selected Model” sought to answer the question that … How did the Andalusian poets in the ccollection structuredtheir Eulogies poems? This question has been answered through the study of some of the structures that bring the form of the Andalusian Poem in the collection to the mind of the recipient, through the study of the structure of the address, the technical structure, and the synthetic structure, which recorded a noticeab presence of the Andalusian Poem in the collection.